Fatores motivacionais, ansiedade e desempenho técnico em equipes de diferentes categorias em um jogo de futsal - SILVA, Carlos Adriano Pereira da (2024)
Objective: To identify the prevalence of motivational factors, anxiety and technical performance in teams from different categories in a futsal game. Materials and Methods: The sample consisted of three futsal teams from São Luís - MA. With the following characteristics: under-20 category, formed by 12 players, mean age in years of 19.5 ± 0.67, practice time of more than three years, training frequency per week of 33.33% for 4 days and 33.33% for 2 days, training duration in 66% between 1 to 2 hours; adult category, formed by 14 players, mean age in years of 25.3 ± 5.54, practice time of more than three years, frequency of training in the week from 50% to 5 days, duration of training in 42.85% between 2 to 3 hours; university category, formed by 9 players, mean age in years of 23.9 ± 3.95, practice time of more than three years, frequency of training in the week of 44.44% for 2 days, duration of training in 55% for less than 1 hour. For technical performance, the games were filmed and later quantified the right and wrong passes, right and wrong finalizations and tackles made; The Participation Motivation Questionnaire (PMQ) and Competitive State Anxiety Inventory-2 (CSAI-2) questionnaires for anxiety were applied. Results and Discussion: The following values were observed in the game of each category: sub-20; 304 passes performed, 86.51% of which were correct passes and 13.49% were incorrect passes, with the majority of passes performed in the backcourt; 46 finalizations made, of which 93.48% were wrong and 6.52% were right and 39 tackles were made: adult; 350 passes made, with a percentage of 89.71% correct passes and 10.29% wrong passes, with a predominance of passes made in the backcourt; 28 finalizations made, with 3.57% of finalizations correct and 96.43% of finalizations wrong and 34 tackles made: university; 178 passes made, of which 92.13% were correct passes and 7.87% were wrong passes, predominating passes made in the backcourt; 41 finalizations made, with 12.20% of correct finalizations and 87.80% of wrong finalizations and 31 tackles made. As for motivational factors, the technical competence and competition domains obtained higher values in the sub-20 and adult category, while in the university category the highest values were the physical fitness and competition domain. The three categories showed low values for somatic anxiety and cognitive anxiety and high values for self-confidence. Conclusion: In the present study, there was a better use of the players/team regarding the right passes in relation to the wrong ones, little efficiency in the finalizations carried out and a high percentage of wrong finalizations in the three categories. The defense court was the place with the highest incidence of tackles. Predominance of self-confident profile and low anxiety in teams.